2014
DOI: 10.1111/jgh.12643
|View full text |Cite
|
Sign up to set email alerts
|

Clinical association between non‐alcoholic fatty liver disease and the development of hypertension

Abstract: Development of hypertension is more potentially associated with the more progressive NAFLD than normal or milder state. In addition, NAFLD was an independent risk factor for hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
70
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 38 publications
5
70
1
5
Order By: Relevance
“…In a large occupational cohort of Korean men, baseline NAFLD was prospectively associated with incident hypertension [27]. Another study of this Korean cohort, including both men and women, also showed that NAFLD was associated with the new onset of hypertension [28].…”
Section: Discussionmentioning
confidence: 99%
“…In a large occupational cohort of Korean men, baseline NAFLD was prospectively associated with incident hypertension [27]. Another study of this Korean cohort, including both men and women, also showed that NAFLD was associated with the new onset of hypertension [28].…”
Section: Discussionmentioning
confidence: 99%
“…Supporting a dose-response relationship, the investigators reported that hypertension was particularly common in those who had moderate-to-severe NAFLD at baseline. 93 So closely are increased serum uric acid (SUA) levels associated with other features of the MetS [94][95][96][97][98] that they can be considered an additional feature of the MetS. There is a graded, positive association between SUA levels and NAFLD severity and elevated SUA levels predict NAFLD risk independently of coexisting MetS features in different ethnicities.…”
Section: Metabolic Syndromementioning
confidence: 99%
“…A recent retrospective cohort study conducted in 11,448 South Korean people without hypertension at baseline elegantly supports the notion that development of new or resolution of pre-existing fatty liver over 5 years strongly affects the risk of incident hypertension 92 . Another large prospective cohort study has shown that the risk of developing hypertension increased substantially in those with NAFLD and the risk, although attenuated, remained significant after adjustment for covariates 93 . Supporting a dose-response relationship, the investigators reported that hypertension was particularly common in those who had moderate-to-severe NAFLD at baseline.…”
Section: Metabolic Syndromementioning
confidence: 99%
“…Furthermore, several studies have shown that HTN was independently associated with non‐alcoholic fatty liver disease , which is a major risk factor for chronic liver disease worldwide . Patients with non‐alcoholic fatty liver disease might progress to cirrhosis, fibrosis and liver failure, which can subsequently result in poor graft function .…”
Section: Discussionmentioning
confidence: 99%